Study of apple packaging material properties by using parchment and recycled paper - Rahmad, R.; Abdul Rahman, Z.A.R (UTHM Publisher, 2018)
This paper investigated the potential properties of apple packaging material used as a major ingredient for promoting eco-friendly apple packaging materials. In addition, old newspapers and parchment paper were used as specimens to assess natural behavior of the apple packaging material. The main objective was to determine the mechanical properties of the paper with different amount or the different percentage of parchment paper and recycled paper compositions. The response of this study was identifying the tensile strength, bursting strength and tearing strength factor. The results showed production of papers from parchment paper and recycled paper affects the strength of the paper itself. The increase in the percentage of recycled paper has resulted in the mechanical properties of ascending paper. The combination of 60% recycled paper and 26% parchment paper produces the best mechanical properties with tear strength of 25.1 N. Meanwhile the composition of 43% parchment paper, 43% recycle paper and 14% of potato flour resulted with 856.0 kPa burst strength and 224.0 N tensile strength. The conclusion suggests that the combination of recycled paper and parchment paper can be one of the alternative raw materials used to package an apple